TRADITIONAL INDUSTRIES IN THE COLONIAL PERIOD: THE ECONOMIC ACTIVITIES OF THE PEOPLE OF TEGAL IN THE FIRST HALF OF THE 20TH CENTURY (History Department, Semarang State University and Historian Society of Indonesia, 2019)
During the colonial government, the emergence of an industrial sector in economic system cannot be separated from the desire to meet the needs of international commodities. Non-agricultural economic activities occupied by Tegal rural communities were grown and developed, especially those related to world markets. The purpose of this study is to uncover the industrial dynamics of the Tegal people, social conditions of the people in it, the synergy of the colonial industry with the people's industry. Historical method with the approach of the social sciences used as an analytical tool various conditions in rural areas. The results of the study show that non-agricultural people's economic activities in Tegal, had existed long before the colonial period and grew. Its existence is widely used for colonial interests. While the consideration of the colonial government placing various industries in Tegal is, strategic position, economic infrastructure, regional potential.Keywords: Colonial Government, Synergy, People's Industry Pada masa pemerintah kolonial, munculnya suatu sistem perekonomian sektor industri tidak bisa dilepaskan dari keinginan untuk mencukupi kebutuhan komoditas dunia internasional. Kegiatan ekonomi non pertanian, yang telah ditekuni oleh masyarakat pedesaan Tegal semakin ditumbuhkan, khususnya yang terkait dengan pasar dunia. Tujuan dari penelitian ini adalah mengungkap dinamika industri rakyat Tegal, kondisi sosial masyarakat di dalamnya, sinergitas industri kolonial dengan industri rakyat. Metode historis dengan pendekatan ilmu-ilmu sosial, dipakai sebagai alat analisis berbagai kondisi di wilayah pedesaan. Hasil penelitian menunjukkan bahwa kegiatan ekonomi rakyat non pertanian di Tegal, telah ada jauh sebelum masa kolonial dan tumbuh. Keberadaannya banyak dimanfaatkan untuk kepentingan kolonial. Sementara itu pertimbangan pemerintah kolonial menempatkan berbagai industri di Tegal adalah, posisi yang strategis, infrastruktur ekonomi, potensi wilayah.Kata Kunci: Pemerintah Kolonial, Sinergitas, Industri Rakyat